Excessive Product Packaging and Brand Credibility in The Bottled Water Industry - Nani Suretno; Willy Abdillah; Ferry Tema Atmaja (Jurnal Manajemen, 2026)
This study investigates the influence of excessive product packaging (EPP) on consumers' perceptions of greenwashing, green confusion, and green skepticism, and their implications for green brand equity (GBEQ), examining brand credibility as a moderator in the Indonesian bottled water market. A quantitative, cross-sectional causal-comparative survey was conducted, with data collected via an online questionnaire distributed to Indonesian consumers who recently purchased AQUA or Le Minerale, using purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 4, with multigroup analysis assessing differences between the two brands. Results show EPP significantly and positively affects greenwashing, green confusion, and green skepticism. Only green skepticism significantly and negatively influences GBEQ, functioning as the sole mediator linking EPP to GBEQ. Contrary to expectations, higher brand credibility strengthens, rather than mitigates, the adverse effect of green confusion on GBEQ. Structural relationships did not differ significantly between AQUA and Le Minerale.